Knowledge about cataract, glaucoma, and age related macular degeneration in the Hong Kong Chinese population. Issue 10 (1st October 2002) - Lau, J T F; Lee, V; Fan, D; Lau, M; Michon, J
Abstract : Aims: Patients' knowledge and participation in their care are important in prevention of blindness from common eye diseases such as cataract, glaucoma, and age related macular degeneration (AMD). The aim of this study was to measure knowledge of these conditions in the Hong Kong Chinese population. Methods: Subjects aged 40 and above in the Shatin district of Hong Kong were randomly selected as part of a larger study of causes of adult visual loss. The subjects received eye examinations in which the primary cause of visual disability was recorded. The respondents were asked by trained interviewers in a standardised fashion about their knowledge of cataract, glaucoma, and AMD. Their answers were rated for accuracy by a senior ophthalmologist. Results: Out of the 2538 eyes examined, 7.0% had visual acuity less than 6/18. Fully 69.6% of the visual disability for those aged 60 or above was caused by cataract, AMD, or glaucoma. Awareness of cataract in particular was high, in that over 90% of respondents had heard of it. However, only 22.9% of them could describe cataract symptoms correctly, and these percentages were even lower in glaucoma (10.2%) and AMD (<1%). Over 40% of subjects did not know that surgery was an appropriate treatment for cataract. Conclusion: This sample of the Hong Kong Chinese population had limited knowledge of common eye diseases. Educational programmes to enhance public awareness may be needed to improve the effectiveness of health promotion and thus prevent unnecessary blindness.